A Flatworm from the Genus Waminoa (Acoela: Convolutidae) Associated with Bleached Corals in Western Australia - Cooper, C.; Clode, P.; Thomson, D.; Stat, Michael (Nihon Dobutsu Gakkai, 2015)
A flatworm isolated from bleached colonies of the coral Coscinaraea marshae at Rottnest Island, Western Australia, is described using a combination of morphological and molecular systematics. This flatworm shares morphological features characteristic of the genus Waminoa (Acoelomorpha: Acoela), including the presence of two algal symbionts, but appears to have genital regions different from those of other described species of Waminoa. The design of new oligonucleotide primers enabled the amplification of partial 18S rDNA of the Rottnest Island acoel specimens, and phylogenetic analysis positioned them within Waminoa, confirming their placement in the genus. Furthermore, Waminoa specimens from Rottnest Island grouped into a sister clade to Waminoa brickneri, indicating that the morphological and genetic differences observed are most likely intraspecific and due to geographic variation. As such, we name these Rottnest Island specimens W. cf. brickneri, but highlight that key differences warrant further exploration before assignment to this species can be confirmed. This is the first acoel flatworm described from Western Australia and contributes to our understanding of the diversity and evolutionary relationship of the Acoela.